2008
DOI: 10.2214/ajr.07.4037
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Management of Hypervascular Osseous Metastasis: Role of Embolotherapy Before Orthopedic Tumor Resection and Bone Stabilization

Abstract: The results of this study support the concept that there is no statistically significant difference among amounts of intraoperative EBL with varying degrees of embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 21 publications
2
34
1
9
Order By: Relevance
“…No agreement exists on the effect of degree of devascularization on estimated blood loss. Some authors suggest that tumor devascularization reduces estimated blood loss [2,4,6,16]; however, some have found no correlation between tumor devascularization and estimated blood loss [7]. In our study, we found no correlation between degree of devascularization and estimated blood loss.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…No agreement exists on the effect of degree of devascularization on estimated blood loss. Some authors suggest that tumor devascularization reduces estimated blood loss [2,4,6,16]; however, some have found no correlation between tumor devascularization and estimated blood loss [7]. In our study, we found no correlation between degree of devascularization and estimated blood loss.…”
Section: Discussioncontrasting
confidence: 92%
“…Little consensus exists in the literature regarding the effect of tumor size on estimated blood loss. Sun and Lang [16] reported a weak correlation (r 2 = 0.02) between tumor size and estimated blood loss, whereas Kickuth et al [7] found a moderate correlation (r = 0.51). We found a strong correlation between tumor size and estimated blood loss on multivariate analysis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This helps in decreasing the size of the tumor and reduction in the vascularity of the tumor. The margins between the tumor and the surrounding tissues become better-delineated thus facilitating surgically safe resection and also reduce the operative time thereby decreasing the intra-operative blood loss (26,27) . This is particularly important that high transfusion requirements in patients undergoing tumor resection is complicated by coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Hypervascular lesions most often embolized are renal cell carcinomas, germ cell tumors, and thyroid carcinomas. [14] At our center, consideration is given to preoperative embolization primarily for those spinal tumors that demonstrate avid enhancement on MR imaging or for patients who have a positive history of renal cell carcinoma. In our study, we sought assess the role of presurgical embolization for the main purpose of reducing intraoperative blood loss to improve surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%